IMPACT OF LASER LEVELING TECHNOLOGY ON WATER USE EFFICIENCY AND CROP PRODUCTIVITY IN THE COTTON –WHEAT CROPPING SYSTEM IN SINDH - Shahani, Wajid Ali; Kaiwen, Feng; Memon, Aslam (International Journal of Research -GRANTHAALAYAH, 2016)
The crop productivity in Pakistan is very low as majority of the farmers are still practicing traditional farming techniques. The existing crop production technologies do not offer effective and efficient utilization of natural resources, particularly that of water. Moreover, a significant amount of irrigation water is wasted due to uneven fields and ditches. Unevenness of the soil surface also has a major impact on the germination, stand and yield of crops through nutrient water interaction and salt and soil moisture distribution pattern. Therefore, the water use efficiency along with yield per acre could be increase by adopting resource conservation technologies like laser leveling. A sample of 120 growers including 60 wheat growers and 60 cotton growers were selected from Mirpurkhas & Tando Allahyar districts of Sindh province of Pakistan. Study results revealed that about 21 percent irrigation water saved by the adoption of laser leveling technology and also obtained higher yield and profit margins comparatively. Study concluded that adoption of laser leveling technology helps in reducing the farm input costs, improve water use efficiency and enhance crop productivity.